Bilateral spontaneous pneumothorax in undiagnosed asthma in an adult: Bilateral spontaneous pneumothorax in acute asthma attack - Tavornshevin, Pipu; Kongpolprom, Napplika (Clinical Critical Care, 2025)
Introduction: Bilateral spontaneous pneumothorax (BSP) is a rarely observed complication during an acute asthma attack. However, it can cause serious respiratory distress and must be rapidly treated. Case presentation: A middle-aged male patient and active smoker with no previous medical illnesses presented to the emergency room, reporting severe dyspnea over the past 3 days. His vital signs were unstable, with severe desaturation (85% in room air). Physical examination revealed hyperresonance on percussion, diminished breath sounds in both lungs, and diffuse polyphonic wheezing. Chest X-ray displayed a moderate to large amount of bilateral pneumothorax with partially collapsed lungs. Thoracic computed tomography confirmed bilateral pneumothorax without evidence of cystic lung lesions or subpleural blebs. Importantly, imaging revealed diffuse mild bronchial wall thickening, indicative of chronic airway inflammation. The patient underwent treatment with bilateral tube thoracostomy and systemic corticosteroids. His treatment was maximized to control airway inflammation. Conclusions: Acute asthma attacks can worsen due to disease progression or complications from other conditions mimicking asthma symptoms. BSP or unilateral spontaneous pneumothorax is a rare condition observed during an acute asthma attack, but it can be life-threatening. Delayed treatment and misdiagnosis may lead to serious respiratory distress and even death.